Influence of myocardial damage on serum procalcitonin in ST-elevation myocardial infarction. (25th November 2020) - Reindl, M; Tiller, C; Holzknecht, M; Lechner, I; Henninger, B; Mayr, A; Brenner, C; Klug, G; Bauer, A; Metzler, B; Reinstadler, S.J
Abstract: Background: Myocardial tissue injury due to acute ST-elevation myocardial infarction (STEMI) initiates an inflammatory response with a release of systemic inflammatory biomarkers including C-reactive protein (CRP) and white blood cell count (WBCc), which, however, hampers the usefulness of these routine biomarkers to identify concomitant infections. The clinical role of Procalcitonin (PCT), a promising marker of bacterial infections, to detect concomitant infections in acute STEMI is unknown, mainly because it is unclear whether myocardial injury per se induces a systemic PCT release. Purpose: To investigate release kinetics of serum PCT in the acute setting of STEMI and possible associations with myocardial injury markers as comprehensively assessed by cardiac magnetic resonance (CMR) imaging. Methods: In this prospective observational study, we included 141 STEMI patients treated with primary percutaneous coronary intervention (PCI). Concentrations of PCT, high-sensitivity CRP (hs-CRP), WBCc and high-sensitivity cardiac troponin T (hs-cTnT) were measured serially at day 1 and day 2 after infarction. CMR imaging to assess infarct size (IS), extent of microvascular injury (MVI) and occurrence of intramyocardial haemorrhage (IMH) was performed within the first week following STEMI. Results: Median concentrations of PCT were 0.07μg/l at both time points. In 140 patients (99%), both PCT values were within the normal range (≤0.5μg/l). Whereas hs-CRP, WBCc, and hs-TnT were significantly correlated with CMR markers of myocardial damage, PCT did not show significant correlations (all p>0.10) with IS (PCT24h: r=0.07; PCT48h: r=0.13) or MVI (PCT24h: r=−0.03; PCT48h: r=0.09). Furthermore, PCT failed to discriminate between large and small IS or MVI or between presence and absence of IMH (AUC values:0.46–0.55). Conclusions: In the acute phase after PCI for STEMI, circulating PCT remained unaffected by the extent of myocardial and microvascular tissue damage as visualized by CMR imaging. These data highlight the clinical potential of PCT to identify concomitant infections and to guide antibiotic treatments in STEMI patients. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Austrian Science Fund, Tiroler Wissenschaftsförderung